2021
DOI: 10.3389/fbioe.2021.615920
|View full text |Cite
|
Sign up to set email alerts
|

FBS-Derived Exosomes as a Natural Nano-Scale Carrier for Icariin Promote Osteoblast Proliferation

Abstract: Icariin is a class IV drug of low solubility, permeability, and poor bioavailability. Synthetic nanomaterials have developed rapidly. However, some literatures point out that synthetic nanomaterials such as liposomes, aptamers, metal nanoparticles, and nanogels have high toxicity and are affected by the reticuloendothelial system or mononuclear phagocyte system. It is known that exosomes could be used as an ideal clinical drug delivery vehicle to avoid the above-mentioned problems to a certain extent. Studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Because of their ideal characteristics, sEVs are also favorable nanoscale drug carriers for the regeneration of tissues and the treatment of certain diseases ( Liao et al, 2019a ; Elsharkasy et al, 2020 ). For example, Dong et al revealed that the use of fetal bovine serum-derived sEVs to carry Icariin could promote osteoblast proliferation and bone regeneration more effectively than Icariin alone ( Dong et al, 2021 ). Wu et al demonstrated that BMSC-derived sEVs and Fe 3 O 4 nanoparticles under conditions of a static magnetic field could facilitate bone regeneration and enhance wound healing ( Wu et al, 2020 ; Wu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because of their ideal characteristics, sEVs are also favorable nanoscale drug carriers for the regeneration of tissues and the treatment of certain diseases ( Liao et al, 2019a ; Elsharkasy et al, 2020 ). For example, Dong et al revealed that the use of fetal bovine serum-derived sEVs to carry Icariin could promote osteoblast proliferation and bone regeneration more effectively than Icariin alone ( Dong et al, 2021 ). Wu et al demonstrated that BMSC-derived sEVs and Fe 3 O 4 nanoparticles under conditions of a static magnetic field could facilitate bone regeneration and enhance wound healing ( Wu et al, 2020 ; Wu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, emerging evidence indicates that the use of nano‐scale carrier can solve the above problems. For example, Dong reported that FBS‐derived exosomes as a nano‐scale carrier of icariin were more effective than icariin alone in the treatment of bone loss (Dong et al, 2021). Therefore, nano‐antioxidant therapy is to be expected in the future, whether in kidney diseases, toxicity‐related diseases, or other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The first evidence of a relevant improvement in the anticancer activity of ICA-BM is clearly demonstrated in Figure 4, in which the IC 50 of this optimized formulation, a parameter often used to compare the antiproliferative activity and the toxic potential of different antineoplastic drugs [35], is equal to 2.79 ± 0.2 µM, a value ten times lower compared to that of ICA-Raw (22.3 ± 3.4). Most probably the observed enhanced cytotoxic effects observed when employing the optimized formula are coming from the ability of BM to enhance the poor solubility of ICA, ensuring a higher intracellular availability [12]; in fact, despite its promising anticancer activity, ICA is characterized by poor bioavailability due to low solubility and permeability [11]. The relevance of this result is also connected to the fact that cancer patients often encounter severe adverse effects attributable to the necessity of administering high doses of the drug [36], so the development of new formulations able to maximize the clinical efficacy, then reducing the doses, is of great importance.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the above, ICA represents an effective asset against pancreatic cancer. Despite its promising anticancer activity, ICA suffers from the shortcomings of poor bioavailability due to poor solubility and permeability [11]. In this regard, nanocarriers can be of great help, improving the bioavailability of ICA by increasing the solubility and permeability across the biological membranes [12], which could enhance anticancer activity against pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%